On the Problem of “Southern Slavic Influence” on Novgorod Monumental Painting in the Second Half of the 14th century - Nemykina, Elena А. (Actual Problems of Theory and History of Art, 2025)
Many researchers have addressed the problem of influence of the Balkan art on the monumental painting of Novgorod in the second half of the 14th c. But particular parallels which could explain all specific traits of Novgorod’s painting haven’t been found in the Balkan art until nowadays. Besides, there is no common opinion about the general meaning of the term “Southern Slavic influence”. This fact makes it difficult to use this concept for the purpose of iconographic and stylistic analysis, as well as for discussing the problems of chronology, terminology and the contents of Novgorod murals.
Keywords: “Southern Slavic influence”; Novgorod monumental painting; church of Transfiguration in Kovalevo; second half of 14th century